THE ASSOCIATIONS OF AGRICULTURAL PRODUCERS FOR SALE OF AGRICULTURAL PRODUCTS - Istudor, Nicolae (Economics of Agriculture, 2006)
Romanias EU accession will be completed, most probably, in the year 2007, this being more a political action, than an economical one. Still, the accession of Romanias economy to EUs competitive economy will be very difficult (especially the agriculture and food industry). One of the present problems for the agricultural food industry is the production of qualitative uniform products, in quantities large enough to satisfy the demand of 450 million consumers. Thus, establishing associative forms in the production and commercialization of agricultural food products can contribute to the increase in competitiveness of Romanian products on the European market.